PEMAKNAAN SIMBOL DALAM KOMUNITAS ‘BROTHERHOOD’ (Konstruksi Makna Simbol sebagai Identitas Diri dalam Komunitas ‘Brotherhood’ di Bandung) - Ditha Prasanti; Sri Seti Indriani (SEMIOTIKA: Jurnal Komunikasi, 2016)
Culture is reflected in a community, the community itself is created from a group of individuals which have similarities. These similarities can come from the same race, same level of economic, same religion, same political view or the same lifestyle. As social beings, every individual has the urge to have a sense of belonging, a need of self existence, humans also need to be accepted by a group of people or community. This 'sense of belonging' is one of the human trait. It gives the satisfaction of self-identification which they can feel as a part of a community, and so they can feel their existency. The Brotherhood community has its own characteristic identity which have been constructed before in Bandung, so it is recognized easily by the people of Bandung. They have the particular identities that range from simbols through attributes in clothing and also motorcycles. Those identities become major simbols as individuals who are members of the Brotherhood community. In this study, researchers used a qualitative approach with descriptive methods. Data collection techniques used were interviews, observation and documentation. The results of this study indicate that in this case the simbols used by the Brotherhood simbolizes 'macho', 'manly' and ‘loyality’.They are identified from the skull emblem, black colour clothing, boots, leather jackets and big classic motorcycles. As a Brotherhood member, he should continue to hold this commitment in accordance with the identity simbol attached to him, he has to look macho, manly and loyal. Keywords: Meanings, Simbol, Community Brotherhood